Antisense transcription from lentiviral gene targeting linked to an integrated stress response in colorectal cancer cells - Taekyu Ha; Michael DiPrima; Vishal Koparde; Parthav Jailwala; Hidetaka Ohnuki; Jing-Xin Feng; Murali Palangat; Daniel Larson; Giovanna Tosato (Elsevier, 2022)
Advances in gene therapy research have resulted in the successful development of new therapies for clinical use. Here, we explored a gene targeting approach to deplete ephrinB2 from colorectal cancer cells using an inducible lentiviral vector. EphrinB2, a transmembrane ephrin ligand, promotes colorectal cancer cell growth and viability and predicts poor patient survival when expressed at high levels in colorectal cancer tissues. We discovered that lentiviral vector integration and expression in the host DNA frequently drive divergent host gene transcription, generating antisense reads coupled with splicing events and generation of chimeric vector/host transcripts. Antisense transcription of host DNA was linked to development of an integrated stress response and cell death. Despite recent successes, off-target effects remain a concern in genetic medicine. Our results provide evidence that divergent gene transcription is a previously unrecognized off-target effect of lentiviral vector integration with built-in properties for regulation of gene expression.